Revisiting the Understanding and Translation Issues of "Disorder of Loneliness" - Xugao HAN; Dong CHEN; Xiaoke ZHAO; Zhen LIU (Yixue yu zhexue)
It is widely acknowledged in academia that both "disorder of loneliness" and "discord of self-containment" originated from E. Bleuler's term "autism". However, few scholars have noted that the earlier source of "autism" can be traced back to Freud's concept of "auto-eroticism". To thoroughly resolve the issue of the mixed usage of the two translations of "autism", it is necessary to conduct an in-depth analysis of Freud's concepts of auto-eroticism and narcissism, exploring their influence on Bleuler's pioneering concept of "autism". Furthermore, based on the diagnostic criteria outlined in the 2024 Chinese version of the Diagnostic and Statistical Manual of Mental Disorders (5th edition, revised), a detailed interpretation of its core symptoms is required to fundamentally clarify the essence of autism. This will provide more substantial support for translating it as "discord of self-containment". From a refutational perspective, this study further demonstrates the limitations of the argument for using "disorder of loneliness" as the translation proposed by scholars such as Yu Songmei. This paper advocates for the unified adoption of "discord of self-containment" as the correct translation, supported by a more comprehensive historical and theoretical basis.